Australian experience with total pancreatectomy with islet autotransplantation to treat chronic pancreatitis. Issue 12 (6th May 2021) - Bampton, Tristan J.; Holmes‐Walker, D. Jane; Drogemuller, Chris J.; Radford, Toni; Anderson, Patricia; Etherton, C.; Russell, C. H.; Khurana, S.; Torpy, David J.; Couper, J. J.; Couper, R. L. T.; Macintyre, Pamela; et al.
Abstract: Background: This study aimed to describe the clinical outcomes of total pancreatectomy with islet autotransplantation (TP‐IAT) in Australia. Methods: Individuals selected for TP‐IAT surgery according to the Minnesota Criteria (Appendix) without evidence of diabetes were evaluated including time to transplantation from pancreatectomy, islet numbers infused and post‐transplantation HbA1c, C‐peptide, total daily insulin and analgesic requirement. Results: Sixteen individuals underwent TP‐IAT from Australia and New Zealand between 2010 and 2020. Two recipients are deceased. The median islet equivalents/kg infused was 4244 (interquartile range (IQR) 2290–7300). The median C‐peptide 1 month post‐TP‐IAT was 384 (IQR 210–579) pmol/L and at median 29.5 (IQR 14.5–46.5) months from transplant was 395 (IQR 139–862) pmol/L. Insulin independence was achieved in eight of 15 (53.3%) surviving recipients. A higher islet equivalents transplanted was most strongly associated with the likelihood of insulin independence ( P  < 0.05). Of the 15 surviving recipients, 14 demonstrated substantial reduction in analgesic requirement. Conclusion: The TP‐IAT programme in Australia has been a successful new therapy for the management of individuals with chronic pancreatitis including hereditary forms refractory to medical treatment to improve pain management with 50% insulin independence rates. Abstract : This study describes the Australian experience of total pancreatectomy with islet autotransplantation. Sixteen individuals underwent total pancreatectomy with islet autotransplantation in Australia from 2010 to 2020.